Construction of a statistical three-dimensional model of the human diaphragm on the basis of tomogrpahy findings - Аврунін, О. Г.; Tymkovych, M. Y.; Dudenko, V. G.; Kurinnyi, V. V. (Deutscher Wissenschaftsherold German Science Herald № 3/2017, 2017)
The work is devoted to the construction of a statistical three-dimensional model of the human diaphragm based on computed tomography data. As a result of the study, a statistical computer model of the human diaphragm was obtained, which in the future will allow us to classify the anatomical structure of the patient's diaphragm and identify possible deviations, as well as the peculiarities of their occurrence.
Keywords: brain; computed tomography; statistical modelling; reconstruction